2011
DOI: 10.1249/mss.0b013e3182106d81
|View full text |Cite
|
Sign up to set email alerts
|

Association of Military Training with Oxidative Stress and Overreaching

Abstract: The sustained training load during the last 4 wk of BT led to oxidative stress observable both at rest and after submaximal exercise. Increased oxidative stress may be a marker of insufficient recovery leading possibly to OR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 33 publications
(44 reference statements)
2
33
0
4
Order By: Relevance
“…Phagocytic cells (e.g., neutrophils, monocytes and macrophages) that infiltrate damaged muscle fibres and other active tissues during exercise may generate large quantities of ROS that deplete extracellular antioxidants, promoting the activity and release of endogenous antioxidants into the circulation. The resulting changes in resting oxidative stress may also modulate the acute oxidative stress response to exercise, with reports of exaggerated (Palazzetti et al 2003;Tanskanen et al 2011) and suppressed (Tanskanen et al 2010) oxidative stress observed following acute exercise challenges in athletes undergoing IT. These inconsistencies can be attributed to the range of study designs utilised, with respect to the duration and intensity of the IT period, and also the timing of blood measures following the change in overload stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Phagocytic cells (e.g., neutrophils, monocytes and macrophages) that infiltrate damaged muscle fibres and other active tissues during exercise may generate large quantities of ROS that deplete extracellular antioxidants, promoting the activity and release of endogenous antioxidants into the circulation. The resulting changes in resting oxidative stress may also modulate the acute oxidative stress response to exercise, with reports of exaggerated (Palazzetti et al 2003;Tanskanen et al 2011) and suppressed (Tanskanen et al 2010) oxidative stress observed following acute exercise challenges in athletes undergoing IT. These inconsistencies can be attributed to the range of study designs utilised, with respect to the duration and intensity of the IT period, and also the timing of blood measures following the change in overload stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…w sta nie prze mę cze nia i prze treno wa nia (ang. over re aching and over tra ining), gdzie jest ob ser wo wa ny wy so ki po ziom wskaź ni ków stre su oksy da cyj ne go [41,42].…”
Section: Rons and Antioxidantsunclassified
“…W 2000 ro ku, na ła mach Na tu re, Fin kel i Hol bro ok [43], opiera jąc się na kon cep cji zja wi ska hor me zy, wy ra zi li pogląd, że naj lep szą stra te gią an ty ok sy da cyj ną jest stałe na ra ża nie or ga ni zmu na RONS, na to miast ha moresign from using antioxidants in sport. Currently, antioxidants are used in sport in specific situations, i.e., in case of overreaching and overtraining, where there is an observed high level of oxidative stress indicators [41,42].…”
Section: Rons I Zja Wi Sko Hor Me Zyunclassified
See 2 more Smart Citations